(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Air conditioning and cooling systems could be negatively influenced by the external conditions, and it is quite possible that this harmful effect reduces the performance of these systems. This is because these unites requiring the outside temperatures to be lower than the heat being released from them. Unfortunately, this would not work in a favor of saving energy. To avoid low efficiency and to maintain high performance of the cooling system, those devices should be carefully selected based on experimental studies undergoing different local conditions. This humble article aims to experimentally investigate the effect of changing the external operating conditions on the performance of a compressive cooling system. The test facility was designed and arranged to simulate the external operating conditions. The outside conditions surrounding the condenser (such as speed of air movement, external air temperature) were varied, and accordingly the pressures and temperatures of specific points in the system were measured. This study has found that the speed of air movement and high temperature of air ambient negatively influenced the performance of the cooling system. The optimum value of the performance of the compressive cooling system obtained at the external air temperature range of (18 → 28 C°). Additionally, the research suggested that the relative humidity of the atmosphere should exceed 50% for this case of study. Therefore, selecting a suitable place for the compressive cooling system is crucial to attain a better performance with less consumption of electricity.